Pengaruh Investment Opportunity Set, Likuiditas, dan Ukuran Perusahaan Pada Kualitas Laba - Jaya, Kadek Agustina Anggara; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2017)
ABSTRACT This research analyzes the effect of investment opportunity set, liquidity, and firm size on earnings quality. Earnings quality is the quality of earnings information presented in the financial statements which reflects the actual performance of the firm. The quality is reflected in the investors’ responses on earnings publication. In this research, earnings quality is measured by earnings response coefficient. Abnormal return in the earnings response coefficient measurement is calculated by market-adjusted model with publication date as event date and five-day event window around the publication date. The calculation uses 20 quarterly earnings figures. The estimation of unexpected earnings uses random walk model, in which it is measured as the difference between current and previous earnings per share scaled by total equity. Investment opportunity set is measured by market-to-book value of assets. Liquidity is measured by current ratio and firm size is measured by the natural logarithm of total assets. Sample consists of 84 companies selected from companies listed in the Indonesian Stock Exchange as at end of 2015 using the proportional stratified random sampling method. The analytical technique used is multiple regression analysis. The results of the analysis show that investment opportunity set negatively affects earnings quality, liquidity does not affect earnings quality, and firm size positively affect earnings quality. Keywords: Earnings Quality, Earnings Response Coefficient, Investment Opportunity Set, Liquidity, Firm Size.